Sur deux esthétiques baroques : le mouvement de l’Histoire dans Richard III de Shakespeare et Marie Stuard de Regnault - Anne Teulade (Etudes Epistémè, 2006)
This essay deals with two historical dramas, Shakespeare’s Tragedy of King Richard the Third, and Charles Regnault’s Marie Stuard. In order to understand why and how they could be termed baroque, this essay studies the representation of « historical motion » on several levels — in the plots, in the words of the characters and in the virtual images they convey — and aims at demonstrating that the two plays are baroque precisely because the temporality represented on stage and the vision of time as it is formulated by the characters are of a different kind: the narrative material overflows the dramatic form.